2016
DOI: 10.4236/apm.2016.68045
|View full text |Cite
|
Sign up to set email alerts
|

Loops in Digraphs of Lambert Mapping Modulo Prime Powers: Enumerations and Applications

Abstract: For an odd prime number p, and positive integers k and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…By Theorem 2.7, G(g, p k ) contains p k +1 2 fixed points. Also by Lemma 1 [9], ord p k g = 2. Hence by Proposition 3.1, there exists no cycle of length > 1.…”
Section: Enumeration Of Cyclesmentioning
confidence: 82%
See 1 more Smart Citation
“…By Theorem 2.7, G(g, p k ) contains p k +1 2 fixed points. Also by Lemma 1 [9], ord p k g = 2. Hence by Proposition 3.1, there exists no cycle of length > 1.…”
Section: Enumeration Of Cyclesmentioning
confidence: 82%
“…Suppose p ∤ g but g 2 ≡ 1 (mod p). Since g = 1 be any integer, so by Lemma 1 [9], g = p k − 1. Then by Theorem 2.3 (4), if t is odd and g = p k 1 then f (t) = p k −t and if t is even then f (t) = t. Suppose that there exists a cycle of length 2.…”
Section: Enumeration Of Cyclesmentioning
confidence: 99%
“…In 1993 it was revealed that the Lambert function gives an exact solution to the quantum-mechanical double-well Dirac delta function model for equal charges [3]. In 2016 Khalid and Lubna proposed loops in digraphs of Lambert Mapping modulo of prime powers and its applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…d. d ≡ t4 (mod r e ). Now we must demonstrate that ḋ ≡ (-1) m d (mod r e ),ḋ ≡ m 2 (-h) m (mod r e )(31)≡ m 2 (-1) m h m (mod r e )(32)≡ (-1) m m 2 h m (mod r e ) (33)≡ (-1) m d (mod r e ).…”
mentioning
confidence: 99%
“…Further, Currie and Oellarmann introduced the concept of fractional metric dimension for getting more accurate solution of integer programming problem [12]. In [13][14][15][16][17][18][19][20][21][22][23][24][25][26], authors have already proposed several classes of integers based on partitions of integers together with graph structures and their applications in graph labeling. In this paper, we propose and prove generalized formulas of all sequences for local fractional metric dimension over triangular prism.…”
mentioning
confidence: 99%